2019
DOI: 10.1002/anie.201909951
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Rhodium(III)‐Catalyzed Aryl C−H Phosphorylation Enabled by Anodic Oxidation Induced Reductive Elimination

Abstract: Transition metal catalyzed C−H phosphorylation remains an unsolved challenge. Reported methods are generally limited in scope and require stoichiometric silver salts as oxidants. Reported here is an electrochemically driven RhIII‐catalyzed aryl C−H phosphorylation reaction that proceeds through H2 evolution, obviating the need for stoichiometric metal oxidants. The method is compatible with a variety of aryl C−H and P−H coupling partners and particularly useful for synthesizing triarylphosphine oxides from dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 67 publications
2
64
1
5
Order By: Relevance
“…The desired products were obtained with yield up to 99 %. The authors proved that the same procedure could be applied for C(sp 3 Xu and co-workers [47] reported in 2019 an efficient method for the electro-catalyzed phosphorylation of aryl substrates 30 by rhodium (III) (scheme 21). A graphite rod as anode and platinum plates as cathode were used for the electrolysis.…”
Section: C(sp 2 )à P Bond Formationmentioning
confidence: 92%
“…The desired products were obtained with yield up to 99 %. The authors proved that the same procedure could be applied for C(sp 3 Xu and co-workers [47] reported in 2019 an efficient method for the electro-catalyzed phosphorylation of aryl substrates 30 by rhodium (III) (scheme 21). A graphite rod as anode and platinum plates as cathode were used for the electrolysis.…”
Section: C(sp 2 )à P Bond Formationmentioning
confidence: 92%
“…The merger of metal catalysis and electrosynthesis, metalla‐electrocatalysis, has been identified as a powerful strategy towards sustainable synthesis, which was substantiated by electrochemical metal‐catalyzed C−H functionalizations in recent years . Very recently, the groups led by Ackermann and Xu disclosed a new catalytic regime, namely anodic oxidation‐induced reductive elimination, where the electricity not only functions as the terminal oxidant, but is also responsible for anodic oxidation‐induced reductive elimination in rhodium‐catalyzed C−N and C−P bond formations. These findings may lead to new catalytic activities and transformations, which are not possible with common chemical oxidants.…”
Section: Figurementioning
confidence: 99%
“…However,e lectricity has been identified as ac lean redox reagent forC ÀHa ctivations. [43] While electrocatalyzed CÀHa ctivation witnessed considerable advances with the aid of 4d and 5d metals,s uch as palladium, [44] ruthenium, [45] rhodium [46] and iridium complexes, [47] the developmento fc ost-effectivea nd less toxic 3d metals [19a, 48] cobalt, [49] iron, [50] manganese, [50] copper [51] and nickel continue to be scarce, but bear unique potentialtowards ideal resource-economy.…”
Section: Nickela-electrocatalyzed Oxidative Transformationsmentioning
confidence: 99%
“…[49g, j] To gain insights into the mechanism, the modus operandi was also interrogated. Compared with the ruthenium-, [45] rhodium-, [46] iridium-, [47b] cobalt-, [43f, 49] or iron-catalyzed [50] electro-chemicalC ÀHa ctivations,i ntermolecularc ompetition experiments showedt hat electron-poor arenes 18 j reacted preferentially over the electron-rich analogs 18 i,s uggesting rather a base-assisted concerted-metalation-deprotonation (CMD) [56] mechanism (Scheme 10 a). [54] In addition, ak inetici sotope effect (KIE) of k H /k D = 1.1 performed by an in operando approach indicated that the CÀHa ctivation is not kinetically relevant (Scheme 10 ba nd c).…”
Section: Nickela-electrocatalyzed Càhaminationmentioning
confidence: 99%